PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MATEMATIKA DENGAN APLIKASI SAC 3 PADA POKOK BAHASAN LINGKARAN KELAS VIII - Ismail, Sumarno; Yahya, Lailany; Yusuf, Putria (LPPM Universitas Bina Bangsa, 2024)
This research leads to the development of interactive learning media with the Smart Apps Creator 3 application on the subject of class VIII circles. This media was developed using the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development model. The subjects of this research were class VIII students at MTs Al-Mubarak Marisa with a total of 23 students. The average score for all aspects from media experts is 3.72 and the average score for all aspects from material experts is 3.6, so it meets the validity criteria. This interactive learning media has also been tested by class VIII teachers and students at MTs Al-Mubarak Marisa and received teacher responses with an average score for all aspects of 87.5% and student responses with an average score for all aspects of 89. 92% with very positive criteria, so this media is effectively used in mathematics learning